SELECTION OF THE ANTIBACTERIAL THERAPY FOR ACUTE ENTERIC INFECTIONS AMONG CHILDREN (RESULTS OF THE MULTICENTRAL ANALYTICAL RESEARCH) - A.I. Grekova; L.P. Zharkova (Педиатрическая фармакология)
The multicenter pharmacoepidemiological analytical research was carried on to study the selection of the antibacterial therapy for acute enteric infections among children. It turned out that antibacterial medications are unjustifiably often applied when treating children for acute enteric infections. When selecting a therapy, the doctors do not take into consideration the clinical semiology and severity of the clinical course. The selection of antibiotics witnesses the poor knowledge of the doctors in such areas as pharmacodynamics, pharmacokinetics and safety profile of the antimicrobial medications.Key words: acute enteric infections, children, selection of antibacterial medications.